Effect of drugs on virulence factors of candida albicans isolated from oral lesion - Scatena, María Gabriela (2014)
Fil: Scatena, María Gabriela. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Biología Bucal y de Patología Bucal; Argentina.